APLICACIÓN DE MÉTODOS DE ENSEÑANZA EN CIENCIAS SOCIALES Y SU INCIDENCIA EN EL APRENDIZAJE DE LOS ESTUDIANTES. - PAZMIÑO CAMPANA, LIDIA MARISOL (2024)
The application of teaching methods in the different subjects corresponds to more dynamic mechanisms of the teaching-learning process, because they are based mainly on the actions developed by teachers and students. It is common that in most cases teaching methods are not related to learning methods, however, it is very significant that it is known that there is a lot of familiarity and above all they are closely related and form a dialectical unit. When a teaching method is applied, it is essential that many factors be taken into account, such as activities or functions of a logical nature, which affect each stage of the learning process and, at the same time, it is essential that this type be taken as a priority of activities that are created by students. The objective of this scientific article is to investigate fundamental aspects of teaching methods, highlighting its concept and its application in the different stages of learning. Finally, the stages of the learning process are explained and the teaching methods applied in each of them are specified.